Penerapan Prinsip Piercing The Corporate Veil Dalam Kasus Forced Delisting - Apandi, Berlyana Helvy; Putri, Putu Anjani Widhi; Ariputra, Ananda Rifki Ariputra Rifki; Putri, Febrina Milania; Aprilia, Rohmawati Putri (Universitas Semarang, 2023)
The purpose of this research was to analyze the application of piercing the corporate veil principle regarding forced delising issue. which caused losses to investors. The importance of the responsibility of directors in the management of a company can be illustrated in the Principle of piercing the corporate veil, as in the event of a violation or deviation from the duties and obligations of a director which causes losses in the company will be responsible up to his personal assets. This research uses normative juridical legal research methods.. The problem approach used in this research is the statutory approach and the conceptual approach. The novelty of this research lies in an in-depth analysis of the application of piercing the corporate veil principle regarding forced delisting cases, thus providing a comprehensive understanding of whether or not modern corporate principles can be applied in forced delisting cases. So it is hoped that this research can provide more insight about the abuse of authority as directors for personal gain which causes losses is an act that deserves to be accounted for by the directors by referring to the application of the principle of piercing the corporate veil. In this case the directors of the company cannot be held responsible for investor losses caused by the Indonesian Stock Exchange's policy in the form of forced delisting. However, this concept does not apply absolutely because in certain condition it is possible that the Board of Directors cannot be responsible for the loss as long as the Board of Directors can provide opposite otherwise. Tujuan penelitian ini dilakukan untuk menganalisis penerapan dari prinsip piercing the corporate veil pada permasalahan forced delisting yang menyebabkan kerugian bagi investornya. Pentingnya pertanggungjawaban direksi dalam suatu pengurusan perseroan dapat digambarkan dalam Prinsip piercing the corporate veil, seperti pada hal terjadinya sebuah pelanggaran atau penyimpangan dari tugas dan kewajiban seorang direksi yang menyebabkan kerugian dalam perusahaan akan menjadi tanggung jawab hingga pada harta pribadinya. Penelitian ini menggunakan metode penelitian hukum yuridis normatif. Pendekatan masalah yang digunakan pada penelitian ini yaitu statuary approach dan conceptual approach. Novelty penelitian ini terletak pada analisis mandalam mengenai penerapan prinsip piercing the corporate veil dalam kasus forced delisting sehingga memberikan pemahaman komperehensif tentang dapat tidaknya suatu prinsip modern perseroan diterapkan dalam kasus forced delisting. Sehingga penelitian ini diharapkan dapat memberikan wawasan lebih mengenai penyalahgunaan wewenang selaku direksi untuk kepentingan pribadi sehingga menimbulkan kerugian yang mana perbuatan tersebut patut untuk dipertanggungjawabkan oleh direksi dengan mengacu pada penerapan prinsip piercing the corporate veil. Dalam permasalahan ini direksi perseroan tidak dapat bertanggung jawab atas kerugian investor yang disebabkan oleh kebijakan Bursa Efek Indonesia yaitu berupa force delisting. Tetapi, konsep tersebut tidak berlaku mutlak sebab pada kondisi tertentu dimungkinkan direksi tidak dapat bertanggung jawab atas kerugian tersebut sepanjang direksi bisa memberikan bukti sebaliknya.